Split Decisions : How and Why to Take a Break from Feminism - Halley, Janet E., 1952- (Book collections on Project MUSE., 2006)
Is it time to take a break from feminism? In this pathbreaking book, Janet Halley reassesses the place of feminism in the law and politics of sexuality. She argues that sexuality involves deeply contested and clashing realities and interests, and that feminism helps us understand only some of them. To see crucial dimensions of sexuality that feminism does not reveal--the interests of gays and lesbians to be sure, but also those of men, and of constituencies and values beyond the realm of sex and gender--we might need to take a break from feminism. Halley also invites feminism to abandon its un.